Angelo - Blake, Quentin (Diamond Books, 1999)
Angelo begins his work restoring the façade of a once glorious church. There, among the sticks and feathers, he discovers a wounded bird. Angelo becomes the bird s reluctant savior.
Keywords: Juvenile literature-Fiction